2015
DOI: 10.1007/s10695-015-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell-specific expression of dead end (dnd) in rare minnow (Gobiocypris rarus)

Abstract: Rare minnow (Gobiocypris rarus) is an emerging model fish in China, and the development of its gonads is still elusive. Germ cell-specific genes are conserved in animals. Dead end (Dnd) was first documented as a germ granule component in zebrafish. Here, we report the cloning and expression profile of dnd in rare minnow. RT-PCR results showed that dnd is expressed specifically in the gonads of both sexes, is maternal in origin and is expressed continuously during embryogenesis. Dnd mRNA could be detected exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, its established role as an anchor for maternal RNAs in unfertilised eggs and polymerization of cortical microtubule arrays has been demonstrated in Xenopus (Mei et al, 2013) needs verification in teleost. The subsequent occurrence of dnd in the embryonic and postnatal germline of G. holbrooki is consistent with those reported for other vertebrates (Youngren et al, 2005;Aramaki et al, 2007) including teleosts (Su et al, 2014;Duan et al, 2015;Wargelius et al, 2016) maintaining germline identity by protecting transcripts from miRNAmediated decay (Ketting, 2007;Goudarzi et al, 2013), FIGURE 7 | Comparative PGC development in representative lecithotrophic and matrotrophic species with increasing level of maternal care. In zebrafish (Raz, 2003;Eno and Pelegri, 2013) and G. holbrooki, PGC markers are compartmentalised in four distinct cells (red dots) by cleavage (8-cell and Cl4, respectively).…”
Section: Pgc Migration Pattern Shares Features Of Both Egg Laying Tel...supporting
confidence: 85%
“…However, its established role as an anchor for maternal RNAs in unfertilised eggs and polymerization of cortical microtubule arrays has been demonstrated in Xenopus (Mei et al, 2013) needs verification in teleost. The subsequent occurrence of dnd in the embryonic and postnatal germline of G. holbrooki is consistent with those reported for other vertebrates (Youngren et al, 2005;Aramaki et al, 2007) including teleosts (Su et al, 2014;Duan et al, 2015;Wargelius et al, 2016) maintaining germline identity by protecting transcripts from miRNAmediated decay (Ketting, 2007;Goudarzi et al, 2013), FIGURE 7 | Comparative PGC development in representative lecithotrophic and matrotrophic species with increasing level of maternal care. In zebrafish (Raz, 2003;Eno and Pelegri, 2013) and G. holbrooki, PGC markers are compartmentalised in four distinct cells (red dots) by cleavage (8-cell and Cl4, respectively).…”
Section: Pgc Migration Pattern Shares Features Of Both Egg Laying Tel...supporting
confidence: 85%
“…In some species, such as mouse and xenopus, dnd expression is sex-dependent [ 13 , 28 ]. However, in fish species, dnd is expressed in both sexes, as observed in this study [ 7 , 13 , 18 , 29 , 30 ]. The expression in both ovary and testis means psdnd has specific roles for oogenesis and spermatogenesis during sexual maturation in starry flounder.…”
Section: Discussionmentioning
confidence: 56%
“…Our WISH results revealed that the psdnd expression pattern was similar with the PGC localization pattern, suggesting that psdnd is a germplasm involved in PGC migration. Similar quantitative and spatial expression patterns occur for dnd in other vertebrate species, including olive flounder, turbot, and rare minnow [ 7 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 83%
“…These mechanisms may involve the vertebrate-specific protein Dead end (Dnd), whose RNA is expressed in the germline of different vertebrate classes, as it has been shown to play a major role in germline development (Aramaki et al, 2007;Duan et al, 2015;Horvay et al, 2006;Wargelius et al, 2016;Weidinger et al, 2003;Youngren et al, 2005). Dnd was shown to protect specific mRNAs from microRNA (miRNA)-mediated inhibition within the germline (Kedde et al, 2007).…”
Section: Introductionmentioning
confidence: 99%